114 A 20-year retrospective study examining outcomes in children and young adults diagnosed with primary thyroid cancer after usual care including invasive surgery and assessing whether a less invasive or watchful-waiting approach would reduce harm. A call for a new thyroid cancer classification in children and young adults. (20th August 2018) - Rosati, Paola; Vito, Rita De; Piga, Simone; Grossi, Armando
Abstract : Objectives: Although paediatric primary thyroid neoplasia (PTN) is a rare event, early over-detection leads to unnecessary invasive surgery. Surgical complications, lifelong monitoring, repetitive radioisotope imaging, and hormone replacement all cause children and parents overstress. Excessive ultra-sonographic screening in the past 15 years has exponentially increased the PTN incidence in children and young adults, leaving mortality unchanged. In 85% of children with PTN, papillary thyroid cancer (PTC) is an indolent lesion of epithelial origin (IDLE) having 99% survival. The term IDLE has still no place in the International Classification of Diseases (ICD-10). To find out whether a less invasive or watchful-waiting approach would reduce harm, overdiagnosis and overtreatment, we collected and analysed retrospectively our 20 year hospital data on children and young adults with PTC treated by usual care (including invasive surgery as in adults) assessing how children and their parents experienced cancer and diagnosis-therapy-related family stress. Method: From a cohort of 45 children with PTN attending our hospital during a 20 year follow-up, we retrospectively analysed variables from the clinical records of 42 children (excluding the 3 with medullary PTN leading to the worst-case scenario). We recorded surgery, clinical complications, histologic PTN findings, including PTC, or IDLE, and follicular thyroid cancer (FTC) histotypes, radioisotope imaging, number of admissions, ICD-10 at the first discharge after surgery, scheduled and unscheduled visits, and deaths. To investigate diagnosis-therapy-related stress, we interviewed children's and young adults' parents about their feelings, depression, requests on diagnostic procedures for siblings, anxiety about school year lost by children or their siblings, distance from hospital, and family economic burden. Primary outcome measures were cancer lesions according to PTN type, patients with PTC who could have undergone less invasive procedures, procedural and social costs, the percentage of parents reporting cancer diagnosis-related stress, and cancer-related mortality. Results: The age at primary PTN diagnosis (PTC and FTC histotypes) was 12.5 years±3.6 SD (range 3.9–17.9). A total 37 patients (88.1%) had histologic findings indicating PTC, namely IDLE, and 5 patients (11.9%) had FTC. Despite these diagnostic findings, all the 42 children underwent total thyroidectomy, in one or two surgical steps (the second step by six months). All the patients' records mentioned the same ICD-10 PTN codification at the first discharge after surgery. Eight children were lost to follow up, one died of FTC (showing 10 years after diagnosis a diffuse metastatic disease), and one of a disease other than PTN. Data for cost-effectiveness and parental answers on diagnosis-, and surgery-related stress are still under analysis and will be presented at the conference. Conclusions: To resolve clinical and social problems related to overdiagnosis and overtreatment in paediatric PTN, hence reducing invasive procedures in children and young adults, complications, overstress, economic costs, and family burden, we need to reappraise the current PTN classification and diagnostic, and procedural existing guidelines, including both children and adults, and establish an international registry reserved to patients under 18 years of age at diagnosis, including an IDLE codification for PTC, who might fare better with less invasive and possible watchful-waiting approaches.